Awareness integration theory A Psychological and genetic path to self-directed Neuroplasticity - Foojan Zeine; Nicole Jafari; Mohammad Nami; Kenneth Blum (Health Sciences Review, 2024)
The self-awareness technique is instrumental in increasing the efficacy of the brain's innate ability to adapt to change via neuroplasticity and self-directing clarity while improving neuro-network paths. The human brain is plastic and capable of modifiability and change, enabling pathway connectivity. This adaptability is affected by both DNA polymorphic antecedents and positive or negative environmental-induced epigenetic-induced alteration of protein transcription. The peripheral part of the brain, capable of neuroplasticity, enables the brain to change and adapt itself to new situations and novel ideas. The brain's neuroplasticity, a capability of the nervous system to change and adapt to external and internal stimuli, can reach a higher efficacy level by applying the awareness integration therapeutical theory. Awareness Integration Theory (AIT) is an evidence-based technique that guides and directs the process of examining thoughts, emotions, behaviors, obstacles, and resistance to plasticity while providing pathways to clarity and self-directed neuroplasticity. By restructuring cognitive/emotional schemas and linking to behavioral pathways, AIT-based therapy expectedly helps create new neural network paths, leading to a renewed functional neural connectivity. As a trauma-releasing approach, AIT revolves around core beliefs, emotions, and bodily attributes to access original memories and moves toward the integration of functional neural networks.